2019
DOI: 10.15421/011915
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temporal patterns of temperature and precipitation on silver Prussian carp (Carassius gibelio) spawning events

Abstract: It was revealed that Gibel carp, Carassius gibelio (Bloch, 1782) spawning phenology is determined by regular patterns of variability in temperature and precipitation over the period of time after spawning in the previous year. The sensitivity to temperature of water as a stimulus to spawning was shown as being dependent on the characteristics of the environment and fish development trajectories over the previous year. Information about fish spawning was collected in the Dnipro-Orylskiy Nature Reserve in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…Knowledge of species' life history can inform biodiversity conservation and our literature review identified a number of applications in which phenology can benefit freshwater conservation. Phenology events can inform invasive species management to identify potential areas susceptible for expansion and methods to control the spread of established introduced species populations (Liang et al 2005, Dexter et al 2015, Gooding et al 2018, Bondarev et al 2019, O'Brien et al 2019, Suresh et al 2019, Giménez et al 2020). Detailed studies on the phenology of imperiled and declining species may also assist in species recovery plans (Gorman and Stone 1999, Joshi et al 2018, Watanabe et al 2020).…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…Knowledge of species' life history can inform biodiversity conservation and our literature review identified a number of applications in which phenology can benefit freshwater conservation. Phenology events can inform invasive species management to identify potential areas susceptible for expansion and methods to control the spread of established introduced species populations (Liang et al 2005, Dexter et al 2015, Gooding et al 2018, Bondarev et al 2019, O'Brien et al 2019, Suresh et al 2019, Giménez et al 2020). Detailed studies on the phenology of imperiled and declining species may also assist in species recovery plans (Gorman and Stone 1999, Joshi et al 2018, Watanabe et al 2020).…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…Therefore, the cumulative sum of precipitation can be considered as a fairly good approximation that characterizes the water balance. The cumulative precipitation indicator gives a smoothed representation of the moisture dynamics (Bondarev et al, 2019;Bondarev and Zhukov, 2017). This indicator also reflects the presence of phenomena of moisture accumulation in the soil and water bodies, which provides a basis for the summation of the precipitation over a period.…”
Section: Discussionmentioning
confidence: 99%
“…It may impact the populations of a variety of native freshwater fish species by directly competing for food, i.e. pelagic zooplankton and benthic invertebrates , or alter the top-down control of zooplankton (Bondarev et al 2019). Specifically, due to competition for food and space, gibel carp are responsible for the disappearance of some native cyprinoid species in some areas, i.e.…”
Section: Modulation Of the Ecological Niche After Invasionmentioning
confidence: 99%